Natural transformation and availability of transforming DNA to Acinetobacter calcoaceticus in soil microcosms. - Nielsen, K M (1997)
A small microcosm, based on optimized in vitro transformation conditions, was used to study the ecological factors affecting the transformation of Acinetobacter calcoaceticus BD413 in soil. The transforming DNA used was A. calcoaceticus homologous chromosomal DNA with an inserted gene cassette containing a kanamycin resistance gene, nptII. The effects of soil type (silt loam or loamy sand), bacterial cell density, time of residence of A. calcoaceticus or of DNA in soil before transformation, transformation period, and nutrient input were investigated. There were clear inhibitory effects of the soil matrix on transformation and DNA availability. A. calcoaceticus cells reached stationary phase and lost the ability to be transformed shortly after introduction into sterile soil. The use of an initially small number of A. calcoaceticus cells and nutrients, resulting in bacterial growth, enhanced transformation frequencies within a limited period. The availability of introduced DNA for transformation of A. calcoaceticus cells disappeared within a few hours in soil. Differences in transformation frequencies between soils were found; A. calcoaceticus cells were transformed at a higher rate and for a longer period in a silt loam than in a loamy sand. Physical separation of DNA and A. calcoaceticus cells had a negative effect on transformation. Transformation was also detected in nonsterile soil microcosms, albeit only in the presence of added nutrients and at a reduced frequency. These results suggest that chromosomal DNA released into soil rapidly becomes unavailable for transformation of A. calcoaceticus. In addition, strain BD413 quickly loses the ability to receive, stabilize, and/or express exogenous DNA after introduction into soil.